2020
DOI: 10.33545/27080013.2020.v1.i2a.17
|View full text |Cite
|
Sign up to set email alerts
|

Constraints and solutions of country bean (Lablab purpureus L.) Production: A review

Abstract: At present food-security and sustainability is a burning issue all over the world. Many indigenous food crops of Bangladesh which promises to ameliorate fruit nutritional food demand and they have the good possibility to develop the world market. Country bean is one of the most important vegetables and pulse crop which have tremendous nutritional value and this crop is cultivated round of the year. Insects, diseases, weeds and soil nutrient management were found as the major barriers for country bean productio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 31 publications
(50 reference statements)
1
10
0
Order By: Relevance
“…Siddika et al [33] observed a positive correlation between seed yield per plant and 100 seed weight. Similar results were also observed by Khan et al [35], Khan et al [40], and Khan et al [41] in legume crop country bean during 2017-2018 in Sylhet, Bangladesh. Table 3.…”
Section: Seed Weightsupporting
confidence: 89%
“…Siddika et al [33] observed a positive correlation between seed yield per plant and 100 seed weight. Similar results were also observed by Khan et al [35], Khan et al [40], and Khan et al [41] in legume crop country bean during 2017-2018 in Sylhet, Bangladesh. Table 3.…”
Section: Seed Weightsupporting
confidence: 89%
“…Farmers from Babati and Kondoa reported attacks by mites. This was also documented by Sarwar (2019) and Khan et al (2020). Despite some mite species being harmful, some species have been described to act as a biological control for other insect pests (Sarwar, 2019).…”
Section: Major Constraints On Lablab Productionmentioning
confidence: 78%
“…Proper identification and characterization of mite species can provide an effective integrated pest management alternative. Sucking bugs have been reported to cause considerable damage to lablab production ( Khan et al, 2020 ). Proper insect pest management of this pest can increase lablab production.…”
Section: Discussionmentioning
confidence: 99%
“…Some pests are attacked the home garden plant [1] [2]. some insects attract in the bean crop and pod [3]- [6], cinnamon plant and fruit [7], chrysanthemum crop and flower [8]; jackfruit plant and fruit [9] [10], mango plant and fruit [11], lemon plant parts [12], okra plant and fruit [13] [14] and so on [15]- [17]. The term is mostly secondhand for individuals that harm crops, cattle and animals, and forests or cause pain to people, especially in their town.…”
Section: Accepted Manuscriptmentioning
confidence: 99%